IMPROVING DEMENTIA THROUGH KINETOTHERAPHY AND MELOTHERAPHY (University Arena, 2025)
Premises: By associating kinetotherapy with melotherapy in dementia patients, a much higher recovery percentage was found.Objectives: The study on the improvement of dementia by recovery started with the establishment of the title of the paper, the study of bibliography, the determination of the hypothesis, the establishment of the place and the period, the groups of patients and methods of recovery.Methods: In this experiment, the following research methods were used: observation, experimental  measurement and recording of data and graphical presentation.Results: Applying an early, gradual and individualized recovery program based on diagnosis, sex, age will shorten the duration of improvement and reintegration into socio-professional activity. Following the recovery process, there was an improvement in physical and mental state. The results of the observations acknowledge this improvement.Conclusions: The findings of the recovery process show improvement of physical and mental state by increasing muscle tone and better articular mobility.